Pemanfaatan Teknologi Dalam Menurunkan Kecemasan Pasien Anak Jelang Tindakan Operasi; Tinjauan Literatur - Puriani, Dewi; Allenidekania, Allenidekania (Universitas Harapan Bangsa Purwokerto, 2020)
Introduction: Anxious and fear in pediatric patients before surgery is a challenge for health workers in the operating room, especially nurses. Various factors cause and ultimately affect the initial period to post-surgery. Distraction techniques have been known to be effective in reducing anxiety in pediatric patients before surgery. The use of technology can be an alternative distraction technique as part of non-pharmacological atraumatic treatment before surgery. The purpose of this study is to identify several non-pharmacological distraction techniques using technology. Method: Literature study was made by analyzing research articles published from 2013 to 2019 and in English. Data obtained from electronic databases Scopus, PubMed, Proquest, ScienceDirect, and Ebsco by using the keywords: